Forecasting Inflation Rate in Padang City Using Backpropagation Method - Atikah; Defri Ahmad (Department of Mathematics, Universitas Negeri Padang (UNP), 2022)
Desire to maximize economic growth in the Padang City, so it need to know the minimum estimate of inflation, that matter is done so that can anticipate the value of inflation outside the desired rate. This research was conducted to obtain forecasting inflation rates in the Padang City using the Backpropagation method. The data of this research is secondary data. Data obtained through the West Sumatra BPS website about inflation of Padang City in January 2013-December 2019. The results of research obtained a forecasting inflation rates in the Padang City with MSE value is 0.010689.